Pengaruh Sosialisasi PP No. 23 Tahun 2018, Modernisasi Sistem Administrasi Perpajakan, dan Biaya Kepatuhan terhadap Kemauan Membayar Pajak pada Wajib Pajak UMKM - Ayem, Sri; Nofitasari, Devi (Unand Press, 2019)
This research aims to investigate the influence of socialization of Government Socialization Regulation number 23 in 2018, modernization of taxes administration system, and cost compliance with the willingness to pay taxes on Micro Small and Medium Business taxpayers. This research is causal association research with a quantitative approach. The population in this research is all of the assessable in Small and Medium Business, which become partners in the Cooperative Office and Micro Small and Medium Business in Special Region of Yogyakarta. The samples of this research are 100 assessable in Micro Small and Medium Business, which taken from the population. The methods used in collecting the data are interviewing. The analysis of multi regression is used to test the hypothesis. The result shows that Government Socialization on Government Regulation number 23 in 2018 has a positive and significant effect on the willingness to pay taxes on Micro Small and Business taxpayers. Modernization of the Tax Administration System has a positive and significant effect on the willingness to pay taxes on Micro Small and Business taxpayers, and Compliance Costs have a negative effect on Willing to Pay Taxes on Micro Small and Business taxpayers. While simultaneously the socialization of Government Regulation Number 23 in 2018, Modernization of the Tax Administration System and Compliance Costs jointly affect the Will to Pay Taxes on Micro, Small, and Medium Business Taxpayers